International labor movement and welfare effects: Malaysia as case study - Hasan, Sharina Farihah; Matsushima, Kakuya; Kobayashi, Kiyoshi (2009)
This paper discusses general equilibrium modeling to measure the quantitative effects of unskilled foreign labors on host country, Malaysia as case study. The model presented in this paper is based on GMig2 model developed using GTAP 7 data base. Two-country, five-sectors and five-factors model is formulated to theoretically signify international labor movement scenario into Malaysia. Assumptions are made for simplification of analysis. Considering Malaysian high reliance on unskilled foreign labor, the model assumed that inflows of foreign labor only involve this type of labor and therefore international movement of skilled labor and issue of brain drain is ignored. The assumptions together with the equations represent basic framework for simulation process using GEMPACK software. Results of the simulation are discussed in two parts. Part 1 looks at the effects of increasing inflow of unskilled foreign labor into Malaysia from year 2005 till 2010. Part 2 of the results discusses policy implementation of reducing the number of unskilled foreign labor to 1.5 million by 2010.